Desafios e possibilidades do uso da experimentação remota no ensino de física na educação básica - Cardoso, Dayane Carvalho (2020)
Remote Experimentation allows teachers and students to access real experiments, through a computer or a mobile device connected to the internet. In this way, public schools students in basic education, for example, may have the opportunity to participate in experimental activities in science laboratories even when the school does not have such laboratories. However, we realize that the adoption, use and dissemination of Remote Experimentation are still challenging, especially for basic education physics teachers. For this reason, we interviewed six basic education teachers to investigate how the challenges and possibilities of using remote experimentation in teaching Physics emerge from their teaching and learning perspectives. As a methodological framework, we use the Comprehensive Interview, which does not use a priori theoretical foundation and aims at a theoretical production based on an articulation between data and hypotheses. Thus, from the preliminary analysis of the interviewees' statements, we realized that the teacher's conception of experimental didactic activities in physics represents a challenge for the appropriation of remote experimentation (RE). Later attentive listening also revealed that other challenges stand out. One of them is the prevalence of a school culture inadequate to today's educational objectives, which reinforces a resistance to innovation in the teaching of physics, especially in the use of RE. Another is the conflict between the wishes and needs of physics teachers and the ability of ERs to satisfy them. The possibilities to overcome these challenges were revealed in the statements of these teachers and aligned with our conceptions. In general, they correspond to a closer relationship between university and school through joint projects.